2014
DOI: 10.1016/j.bbi.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes associated with inflammation in breast cancer patients treated with chemotherapy

Abstract: Inflammation has been associated with fatigue during and after various types of breast cancer treatments. We examined whether prior chemotherapy was associated with DNA methylation patterns that could explain persisting inflammation and/or fatigue in women treated for breast cancer. Prior to breast radiation therapy, DNA was extracted from peripheral blood mononuclear cells (PBMCs) of 61 Stage 0-IIIA breast cancer patients who had received partial mastectomy with or without chemotherapy. DNA methylation was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 49 publications
2
47
0
1
Order By: Relevance
“…In several studies,(2124) genetic and epigenetic mechanisms involved in inflammation were associated with fatigue in oncology patients. Only one study was found that reported on associations between polymorphisms in cytokine genes and decrements in energy in oncology patients undergoing radiation therapy and their family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies,(2124) genetic and epigenetic mechanisms involved in inflammation were associated with fatigue in oncology patients. Only one study was found that reported on associations between polymorphisms in cytokine genes and decrements in energy in oncology patients undergoing radiation therapy and their family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…One implicit assumption is that genetic and epigenetic reprogramming caused by disease states in other tissues are systemically reflected in blood-borne leukocytes. There are numerous published studies examining the response of genome-methylation in whole blood leukocytes to diseases and disease progression (Javierre et al, 2010; Wang et al, 2010; Weiss et al, 2011; Saied et al, 2012; Schroeder et al, 2012; Smith et al, 2012, 2014; Sun et al, 2013; Xu et al, 2013; Almen et al, 2014). However, the genome-wide methylation data from these studies comprises the epigenomic information of several major leukocyte cell types combined as a weighted average of their fractional representation in blood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the period immediately pre-surgery for tumor resection may be assumed to be a relatively stressful period of anticipation, however as opposed to most studies using experimental stressors, no differences in anxiety or cortisol were observed among various stages of ovarian cancer in this period (Schrepf et al, 2013). Other inherent "treatment stressor" studies (i.e., using radiation and chemotherapy) inevitably demonstrate induced inflammatory responses, do not incorporate cancer-free controls, and are beyond the scope of this review (Bower et al, 2011b;Burnette and Weichselbaum, 2013;Liu et al, 2012;Schaue et al, 2015;Smith et al, 2014). The endocrine, inflammatory, and behavioral responses following (select…”
Section: Endocrine Immune and Behavioral Responses To An Acute Strementioning
confidence: 83%